ATP-dependent chromatin remodeling complexes in Drosophila. - Bouazoune, K.; Brehm, A. (Chromosome Research, 2006)
The regulation of chromatin structure is of fundamental importance for many DNA-based processes in eukaryotes. Activation or repression of gene transcription or DNA replication depends on enzymes which can generate the appropriate chromatin environment. Several of these enzymes utilize the energy of ATP hydrolysis to alter nucleosome structure. In recent years our understanding of the multisubunit complexes within which they function, their mechanisms of action, their regulation and their in-vivo roles has increased. Much of what we have learned has been gleaned from studies in Drosophila melanogaster. Here we will review what we know about the main classes of ATP-dependent chromatin remodelers in Drosophila.